(untitled) (American International Journal of Education and Linguistics Research, 2020)
The idea of using language as a tool of communication is the main principle of the communicative language teaching (CLT) approach. English for today (EFT) as a textbook was designed to develop the overall English language competence at a higher secondary level. This paper aims at justifying the suitability of EFT for implementing communicative language teaching in Bangladesh. This study shows English for today is not effective for creating communicative competence among its learners. Moreover, the tertiary students initially face challenges while enrolling in undergraduate programs under the medium of instruction is English. Data have been collected through classroom observation, interviews with teachers, students, and experts. Structured questionnaires for students, teachers, and experts have been used as tools for data collection. Finally, the paper concludes that revised abbreviations may be suitably adaptable to impose a communicative language teaching approach by overcoming the challenges in the large classrooms in Bangladesh.